Pemanfaatan Medan Elektromagnetik untuk Teknologi Wireless Power Transfer - Salsabila Aulia; Sandi Rahyadi; Nadita Dwi Pramestia; Bryant Reza Pahlevi; Diyajeng Luluk Karlina (Pusat Riset dan Inovasi Nasional, 2025)
Wireless Power Transfer (WPT) technology offers a solution to transfer electrical energy wirelessly using electromagnetic fields, providing convenience in charging electronic devices. This technology operates through electromagnetic inductive resonance, enabling efficient power transmission from transmitter to receiver. This article discusses the fundamental mechanisms, practical applications, and technical challenges of WPT. Electromagnetic field safety is a primary concern in the implementation of this technology, especially regarding its impact on health and the environment. With recent innovations and appropriate safety regulations, WPT is expected to become an efficient, safe, and sustainable energy solution across various sectors.